Problematization Methodology: possibilities for training in integrated education (Research, Society and Development, 2022)
Professional education seeks to meet the social and economic demands of society, which requires more and more specific skills and abilities of the subjects to perform critically in the exercise of their profession. Is the problem-solving methodology a possibility and a contribution to the learning process of students in integrated education and vocational education? In this way, this paper intends to characterize the methodology of the problematization and to discuss its theoretical assumptions in the attempt to approach to the conception of critical formation in the integrated education. It was verified that the methodology of the problematization has similar characteristics and adapted to the integrated curriculum of professional education. The research also allowed to identify a possibility for the teaching-learning process, because it takes into account the social reality in which the student is inserted, contextualizing it so that it can build knowledge.